2015
DOI: 10.1016/j.molp.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Stress Modulates the Balance between Exocytosis and Clathrin-Mediated Endocytosis in Arabidopsis thaliana

Abstract: The sessile life style of plants creates the need to deal with an often adverse environment, in which water availability can change on a daily basis, challenging the cellular physiology and integrity. Changes in osmotic conditions disrupt the equilibrium of the plasma membrane: hypoosmotic conditions increase and hyperosmotic environment decrease the cell volume. Here, we show that short-term extracellular osmotic treatments are closely followed by a shift in the balance between endocytosis and exocytosis in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
109
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 105 publications
14
109
1
Order By: Relevance
“…This is in agreement with previously shown involvement of PLDζ2 in auxin carrier relocalization during halotropism (Galvan‐Ampudia et al, ). Also, we found similar initial sorbitol‐induced internalization of PIN2 compared with previously reported PIN2 dynamics after a 10‐min mannitol treatment (Zwiewka, Nodzynski, Robert, Vanneste, & Friml, ). However, although salt induces a relocalization of PIN2 to the lateral membrane compartment, osmotic stress does not have this effect.…”
Section: Discussionsupporting
confidence: 88%
“…This is in agreement with previously shown involvement of PLDζ2 in auxin carrier relocalization during halotropism (Galvan‐Ampudia et al, ). Also, we found similar initial sorbitol‐induced internalization of PIN2 compared with previously reported PIN2 dynamics after a 10‐min mannitol treatment (Zwiewka, Nodzynski, Robert, Vanneste, & Friml, ). However, although salt induces a relocalization of PIN2 to the lateral membrane compartment, osmotic stress does not have this effect.…”
Section: Discussionsupporting
confidence: 88%
“…Although detailed molecular mechanisms linking abiotic stress and endocytosis in plants are lacking, saline or osmotic stress does trigger the activation of endocytic uptake of a biotinylated endocytic marker in rice cells (Bahaji et al, 2003), and overexpression of At-Rab7 increases salt and osmotic stress tolerance, which is consistent with accelerated membrane endocytosis (Mazel et al, 2004). Furthermore, genetic studies have demonstrated the importance of endocytosis for plant fitness under stress (Leshem et al, 2007;Bar et al, 2008aBar et al, , 2008bZwiewka et al, 2015). These observations have led to the hypothesis that plants have developed a more efficient internalization mechanism to retrieve membrane materials to help them adapt to abiotic stress.…”
Section: The Involvement Of Endocytosis In Csc Recyclingmentioning
confidence: 93%
“…Intriguingly, salinity induces a dramatic relocalization of GFP‐tagged ARA6QL protein to the PM, suggesting a function of the protein at the PM under salt stress . A recent study also reports an increase in the size of ARA6‐positive compartments under salt stress , although the implications of this observation have not been followed up. Plants with a functionally compromised VPS9a protein, the Guanine nucleotide exchange factor for the Rab5 homologs, are extremely salt‐sensitive .…”
Section: Intracellular Trafficking and Salt Stressmentioning
confidence: 97%
“…The contribution of CME and CIE pathways to the salt‐induced escalation of endocytosis is an area of active research. Reports of enhanced endocytosis through the clathrin‐mediated pathway are based on the observed rise in clathrin recruitment to the PM , whereas others report that clathrin‐independent pathways are also boosted . Salt‐induced increase in FM4‐64 uptake is observed even in the presence of genetic and chemical perturbation of clathrin although the extent of enhancement is substantially reduced.…”
Section: Salt Stress and Endocytic Response In Plantsmentioning
confidence: 99%